Atividade enzimática em achatina fulica após infecção por angiostrongylus vasorum - NATALIA DO CARMO GONCALVES (2023)
The objective of this work was to characterize the enzymatic activity of N-acetyl-β-Dglycosaminidase -ike (NAG-like) and myeloperoxidase-like (MPO-like) in hemocytes and in tissues of the cephalopodal region of Achatina fulica infected by Angiostrongylus vasorum. 120 Achatina fulica were used: 40 mollusks for the L1 ingestion Group - first stage larvae of A. vasorum; 40 mollusks for the L1 inoculation Group; 40 mollusks for the control Group (Not infected). Mollusks were individually infected with 1000 L1/24h obtained from Baermann's technique from infected dogs according to CEUA_UFMG protocol 227/2022. After infection the mollusks were transferred to aquariums, fed with lettuce and feed containing calcium carbonate and their survival was observed. On the 1st, 8th, and 30th day after infection, hemocyte activation was evaluated by collecting hemolymph by cardiac puncture and one gram of tissue from the cephalopodal region, and enzymatic tests were performed. For the NAG-like and MPO-like tests, 40 mg of tissue was prepared in solutions with similar pH; however, for the N-acetyl-β-D-glycosaminidase assay, the substrate p-nitrophenyl-N-acetyl-β-Dglycosamine was added at 37°c for 10 min and the activity was estimated at 405 nm. For the myeloperoxidase-like enzyme assay the substrate was 3,3', 5,5'- tetramethylbenzidine and the reading revealed at 450 nm. For peroxidase staining 1 x 105 hemocytes hemocytes were monitored for cyanide-resistant peroxidase expression after fixing cells in 4% formalin with acetone for 30 seconds and stained for 10 min in phosphate buffer containing diaminobenzidine 3,3 tetrachlorhydrate (0.25%), hydrogen peroxide (H2O2), potassium cyanide (KCN) - 0.2% under shelter from light. After analysis it was observed that A. fulica challenged by A. vasorum showed similar enzymatic activity to MPO, NAG